Substantial violation of human rights and freedoms as a prerequisite for inadmissibility of evidence - Ablamskyi, S. Ye.; Абламський, С. Є.; Nenia, O. V.; Неня, О. В.; Drozd, V. H.; Дрозд, В. Г.; Havryliuk, L. V.; Гаврилюк, Л. В.; Абламський Сергій Євгенович (Justicia. – 2021. – Vol. 26, № 39 (Enero-Julio). – P. 47-56, 2021)
Метою статті є аналіз різних правових і теоретичних положень, пов’язаних з визначенням правового змісту поняття визнання доказів неприйнятними внаслідок істотного порушення прав і свобод людини.

_The aim of the article is to analyze the various legal and theoretical provisions related to the determination of legal content of the concept of finding evidence inadmissible due to substantial violation of human rights and freedoms. Method_ The authors use general scientific and special methods that enable to obtain scientifically sound conclusions and proposals. In particular, scientific methods, such as dialectical, comparative-legal, system-structural, generalization and logical, are applied. Results_ The problematic issues of the procedure for finding evidence inadmissible due to substantial violation of human rights and freedoms in the criminal proceedings of Ukraine are studied. Some essential violations in collecting evidence by the prosecution are under focus. The ECHR’s case-law with regard to procedure for finding evidence inadmissible is analyzed. The implementation of the doctrine of “fruit of the poisonous tree” and specificity of its application to direct and derivative evidence by domestic courts and the case law of the ECHR is considered. Conclusions_ The authors argue that the investigator is required to comply with the procedure for investigative actions prescribed by the provisions of the CPC of Ukraine in order to ensure human rights and freedoms. The analysis of the application of provisions of the CPC of Ukraine and the ECHR’s case law regarding the issue raised enables to formulate sound conclusions_

Целью статьи является анализ различных правовых и теоретических положений, связанных с определением правового содержания концепции признания доказательств недопустимыми по причине существенного нарушения прав и свобод человека.
Violación sustancial de los derechos humanos y las libertades como requisito previo para la inadmisibilidad de las pruebas
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Україна. Ukraine. Украина; Наукові публікації. Scientific publications. Научные публикации; publikatsii u zarubizhnomu vydanni; publikatsii u WoS; criminal proceedings; substantial violation of human rights and freedoms; inadmissible evidences; pre-trial investigation; court; кримінальне провадження; істотне порушення прав і свобод людини; недопустимі докази; досудове розслідування; уголовное производство; существенное нарушение прав и свобод человека; недопустимые доказательства; суд; досудебное расследование